Disruption of the Gut Microbiota With Antibiotics Exacerbates Acute Vascular Rejection. Issue 7 (July 2018) - Rey, Kevin; Manku, Sukhbir; Enns, Winnie; Van Rossum, Thea; Bushell, Kevin; Morin, Ryan D.; Brinkman, Fiona S.L.; Choy, Jonathan C.
Abstract : Background: The gut microbiota influences many immunological processes but how its disruption affects transplant rejection is poorly understood. Methods: Interposition grafting of aortic segments was used to examine vascular rejection. The gut microbiota was disrupted in graft recipients using an antibiotic cocktail (ampicillin, vancomycin, metronidazole, neomycin sulfate) in their drinking water. Results: Treatment of mice with antibiotics severely reduced total bacterial content in the intestine and disrupted the bacterial composition. Short-term treatment of mice for only the first 3 weeks of life resulted in the population of the intestine in mature mice with bacterial communities that were mildly different from untreated mice, containing slightly more Clostridia and less Bacteroides. Antibiotic disruption of the gut microbiota of graft recipients, either for their entire life or only during the first 3 weeks of life, resulted in increased medial injury of allograft arteries that is reflective of acute vascular rejection but did not affect intimal thickening reflective of transplant arteriosclerosis. Exacerbated vascular rejection resulting from disruption of the gut microbiota was related to increased infiltration of allograft arteries by neutrophils. Conclusions: Disruption of the gut microbiota early in life results in exacerbation of immune responses that cause acute vascular rejection. Abstract : Disruption of mice gut microbiota, either for their entire life or only during the first 3 weeks of life, results in increased acute vascular rejection of allograft arteries due to infiltration of the media by neutrophils. Intima thickening of the arteries reflecting chronic rejection is not affected. Supplemental digital content is available in the text.